Computer delivery of gesture therapy for people with severe aphasia - Marshall, J.; Roper, A.; Galliers, J.; Wilson, S.; Cocks, Naomi; Muscroft, S.; Pring, T. (Psychology Press (Taylor & Francis Group), 2013)
Background: Using gesture as a compensatory communication strategy may be challenging for people with severe aphasia. Therapy can improve skills with gesture, at least in elicitation tasks, but gains ar often modest. Raising the treatment dose with technology might improve outcomes. Aims: This feasibility study developed a computer gesture therapy tool (GeST), and piloted it with nine people who have severe aphasia. It aimed to determine whether practice with GeST would improve gesture production and/or spoken naming. It also explored whether GeST encouraged independent practice and was easy to use. Methods & Procedures: Pilot participants had 6 weeks practice with GeST, flanked by pre- and post-therapy tests of gesture and word production. Usability was explored through interviews and structured observations, and the amount of time spent in the programme was monitored. Outcomes & Results: Scores on the gesture test were evaluated by 36 independent raters. Recognition scores for gestures practised with the tool improved significantly after therapy and the gain was maintained. However, gains were small and only occurred on items that were practised with regular therapist support. There was no generalisation to unpractised gestures and no effect on spoken naming. Usability results were positive. Participants undertook an average of 64.4 practice sessions with GeST, and the average session length was just under 14 minutes. Conclusions: GeST was proved to be easy and enjoyable to use and had some effect on participants’ gesturing skills. Increasing the magnitude of gains would be desirable. The effect on everyday communication needs to be explored.